Enhancement of Adiponectin Ameliorates Nonalcoholic Fatty Liver Disease via Inhibition of FoxO1 in Type I Diabetic Rats - Xiang Xie; Dan Yan; Haobo Li; Qiqi Zhu; Jun Li; Yong-ping Fang; Chi Wai Cheung; Michael G. Irwin; Zhengyuan Xia; Qingquan Lian (Journal of Diabetes Research)
Nonalcoholic fatty liver disease (NAFLD) is a common liver disease which has been previously shown to be associated with type 2 diabetes mellitus (T2DM). Recent research has indicated that type 1 diabetes mellitus (T1DM) is also involved in the development of nonalcoholic fatty liver disease, whereas the underlying mechanisms are largely unknown. Forkhead box O1 (FoxO1) and adiponectin (APN) have been proposed to play an important role in the processes in NAFLD in T1DM. We herein investigated the effects of FoxO1 and APN on the development of NAFLD and the underlying mechanism in streptozotocin-induced T1DM. Serum liver enzymes AST, ALT, and triglyceride (TG) were determined by commercially available kits. Blood glucose levels were measured by the OneTouch Ultra glucose meter. Relevant protein expression was tested by Western blot analysis. Results showed that serum AST, ALT, and TG were all significantly increased in T1DM rats, which was ameliorated by application of APN or selective inhibition of FoxO1 with AS1842856. Moreover, APN and AS1842856 both decreased the expression of liver nuclear FoxO1 which was significantly increased in diabetic rats. However, the inhibition of FoxO1 did not alter the expression of APN and its receptors. We also found that Akt1 expression was significantly declined in diabetic rat which was restored by APN and moderately and significantly increased by FoxO1 inhibition. It is concluded that APN ameliorates NAFLD via inhibition of FoxO1 through Akt1/FoxO1 signaling pathway.